The local magistrates of provincial communities granted with municipal status: A study on the spread of quattuorvirate and duovirate between the late Republican and the Imperial age - Sisani, Simone (Gerión. Revista de Historia Antigua, 2018)
This paper reviews the evidence for the local magistrates of provincial communities granted with municipal (Roman or Latin) status, with particular regard to Cisalpine Gaul, Narbonese Gaul and the Iberian provinces during the late Republican and Augustan age. The analysis allows to formulate new assumptions about the original nature and date of introduction of the duovirate as the typical magistracy of the later municipia.